A convex optimisation approach to robust observer-based H∞ control design of linear parameter-varying delayed systems. (11th November 2008) - Karimi, Hamid Reza; Maass, Peter
This paper presents a convex optimisation method for observer-based control design of LPV neutral systems. Utilising the polynomials parameter-dependent quadratic functions and a suitable change of variables, the required sufficient conditions with high precision for the design of a desired observer-based control are established in terms of delay-dependent parameter-independent linear matrix inequalities. An observer-based controller guaranteeing asymptotic stability of the closed-loop system and satisfying a prescribed level of performance to the LPV neutral system with constant delay parameters is developed. A Lyapunov-Krasovskii method underlies the observer-based H∞ control design. A numerical example with simulation results illustrates the effectiveness of the methodology.